Molecular dynamics simulations of peptide fragments from hen lysozyme: insight into non-native protein conformations. - Smith, L; Mark, A; Dobson, C; van Gunsteren, W (1998)
Molecular dynamics simulations of four peptides taken from the hen lysozyme sequence have been used to generate models for non-native protein conformations. Comparisons between the different peptides and with experimental data for denatured lysozyme and peptide fragments provides insight into the characteristics of the conformational ensembles populated in these non-native states and the dependence of their structural features on the amino acid sequence. For the denatured conformers populated local contacts dominate in determining the properties observed in the trajectories, all four peptides showing similar characteristics. These include a significant increase in the number of main-chain O(i)-NH(i+2) hydrogen bonds and hydrogen bonds involving side-chain groups, this increase compensating to a large extent for the loss of hydrogen bonds involved in helical or beta-sheet secondary structure in the native fold, and the generation of a population of collapsed states with local clusterings of hydrophobic groups. The hydrophobic clusters enable at least partial burial of many side-chains exposed by the loss of tertiary contacts on denaturation and provide models that may explain the experimentally observed protection of amides from hydrogen exchange and the existence of residual secondary structure in non-native species of lysozyme. The results suggest that this approach has an important role to play in aiding the interpretation of experimental data for conformationally disordered non-native states of proteins.